The Correlation between Language Proficiency and the Use of Lexical Collocations by Algerian EFL Undergraduate Students in Essay Writings: a Case Study of Verb+ Noun Collocations - Arabet, Mohamed Akram (Journal of Human Sciences, 2017)
‘Pseudo-native speaker’ is the term given to a foreign language learner who has reached a high level of proficiency. Such level of proficiency is characterised by the mastery of grammar, vocabulary, and pronunciation. Consequently, a distinction must be drawn between grammatical proficiency and the idiomatic one. Idiomaticity has three basic levels of compositionality: free combinations, collocations, and idioms. The present research work investigates the mastery of Verb+Noun lexical collocations by Algerian EFL learners in Frères Mentouri university. It is hypothesised that Algerian EFL learnershave a low level of mastery in the usage and comprehension of Verb+Noun collocations.It is also hypothesised that the essays of Algerian EFL learners lack the use of appropriate Verb+Noun collocations. An online corpus (BNC) and two other online websites (Collocation Checker & O.O.C.D) were used as tools to measure learners’ collocational competence. Examined collocations were extracted from the learners’ examination essays. The analysis was done manually through identification and corpus usage. The findings of the study indicate that Algerian EFL learners have a low competence in dealing with Verb+Noun collocations. Thus, focus on collocational knowledge is required. Teachers must raise their students’ awareness on the importance of collocations in improving the oral and written quality of production. Learners have to, deliberately, be able to identify collocations, and memorise them within their contexts.